2020
DOI: 10.1016/j.jaip.2020.07.005
|View full text |Cite|
|
Sign up to set email alerts
|

Delabeling Delayed Drug Hypersensitivity: How Far Can You Safely Go?

Abstract: Delayed immune mediated adverse drug reactions (IM-ADRs) are defined as reactions occurring more than 6 hours after dosing. They include heterogenous clinical phenotypes that are typically T-cell mediated reactions with distinct mechanisms across a wide spectrum of severity from benign exanthems through to life-threatening cutaneous or organ-specific diseases. For mild reactions such as benign exanthem, considerations for delabeling are similar to immediate reactions, and may include graded or single dose drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 182 publications
(222 reference statements)
1
53
0
Order By: Relevance
“…Antimicrobial drugs are responsible for a significant burden of these reactions; more so in high burden tuberculosis (TB) and human immunodeficiency virus (HIV) settings ( Blumenthal et al, 2019 ). Delayed hypersensitivity reactions to antimicrobials frequently occur in the setting of multidrug regimens e.g., TB infection; and rapid, accurate, and safe diagnostic tools to aid the identification and exclusion of the offending drug are critical ( Lehloenya et al, 2020 ). Drug provocation testing is often considered contraindicated in most settings of severe, life-threatening adverse drug reactions; while systemic reactions to in vivo diagnostics such as patch testing has been reported, especially in the context of HIV infection ( Lehloenya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial drugs are responsible for a significant burden of these reactions; more so in high burden tuberculosis (TB) and human immunodeficiency virus (HIV) settings ( Blumenthal et al, 2019 ). Delayed hypersensitivity reactions to antimicrobials frequently occur in the setting of multidrug regimens e.g., TB infection; and rapid, accurate, and safe diagnostic tools to aid the identification and exclusion of the offending drug are critical ( Lehloenya et al, 2020 ). Drug provocation testing is often considered contraindicated in most settings of severe, life-threatening adverse drug reactions; while systemic reactions to in vivo diagnostics such as patch testing has been reported, especially in the context of HIV infection ( Lehloenya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Delayed hypersensitivity reactions to antimicrobials frequently occur in the setting of multidrug regimens e.g., TB infection; and rapid, accurate, and safe diagnostic tools to aid the identification and exclusion of the offending drug are critical ( Lehloenya et al, 2020 ). Drug provocation testing is often considered contraindicated in most settings of severe, life-threatening adverse drug reactions; while systemic reactions to in vivo diagnostics such as patch testing has been reported, especially in the context of HIV infection ( Lehloenya et al, 2020 ). Thus, in vitro and ex vivo diagnostics are appealing and have been increasingly employed in the evaluation of presumed T-cell mediated hypersensitivity reactions ( Lehloenya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPT should be preceded by a sequential study, including in vitro tests and skin tests, after obtaining informed consent from the patient and family. 6,7 A similar approach to that described above has been proposed and carried out in patients with DRESS syndrome. 8 There are few reported cases of intentional or unintentional reexposure to the drug involved in SCAR, 7,[9][10][11] and even fewer cases in pediatric patients, [12][13][14] mostly with satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A similar approach to that described above has been proposed and carried out in patients with DRESS syndrome. 8 There are few reported cases of intentional or unintentional reexposure to the drug involved in SCAR, 7,[9][10][11] and even fewer cases in pediatric patients, [12][13][14] mostly with satisfactory results. A recent study has shown the ability of high-dose intravenous corticosteroids to reverse the recurrence of symptoms during DPT in patients with SJS and DRESS syndrome, potentially improving the safety of drug rechallenge protocols in these patients.…”
Section: Discussionmentioning
confidence: 99%